USING ECLECTIC APPROACH TO IMPROVE THE STUDENTSâ READING COMPREHENSION - Burhanuddin, Wildhan (Lembaga Perpustakaan Unismuh Makassar, 2012)
The research aimed to find out the improvement of studentsâ reading comprehension in terms of finding main ideas and meaning of words at the studentsâ of SMPN 4 Libureng in the 2012/2013 academic year. This research used A Classroom Action Research that consisted two cycles. The sample of this research consisted of 22 students, those consisted of six women and twelve men .The researcher obtained the data by using reading test and observation sheet. The results of the students reading test in cycle I and cycle II had significantly different scores.Â There was a better increase of gains by students at the end of action in second cycle. In cycle I, the studentsâ achievement of main ideas was 6,09, but after evaluation in cycle II the studentsâ reading comprehension become 7,62.The other hand the studentsâ meaning of words was improved too from cycle I to cycle II, whereas in the studentsâ achievement of meaning of words was 6,13, but after evaluation in cycle II the studentsâ achievement become 7,74. From the findings indicated that there was improvement in the studentsâ reading comprehension from cycle I to cycle II, whereas in cycle I studentsâ achievement reading comprehension was 23,81, but after evaluating in cycle II the studentsâ reading comprehension became 25,69. While the standard target achievement KKM 66. From these findings, the researcher made conclusion that by using an eclectic approach could improve the studentsâ reading comprehension achievement.Â Â Key Word: Eclectic Approach, Improve, Reading ComprehensionPenelitian ini bertujuan untuk mengetahui peningkatan siswa dalam hal pemahaman membaca mencari ide-ide utama dan arti dari kata-kata di siswa SMPN 4 Libureng pada tahun akademik 2012/2013. Penelitian ini menggunakan Penelitian Tindakan Kelas yang terdiri dua siklus. Sampel penelitian ini terdiri dari 22 siswa, mereka terdiri dari enam perempuan dan dua belas orang peneliti dan diperoleh data dengan menggunakan uji membaca dan lembar observasi. Hasil tes membaca siswa pada siklus I dan siklus II memiliki nilai yang berbeda secara signifikan. Ada peningkatan yang lebih baik dari prestasi siswa pada akhir tindakan dalam siklus kedua. Pada siklus I, pencapaian siswa pada ide utama adalah 6,09, tapi setelah evaluasi pada siklus II siswa memahami bacaan menjadi 7,62.The sisi lain makna dari kata-kata siswa itu ditingkatkan juga dari siklus I ke siklus II , sedangkan di siswa pencapaian arti kata-kata itu 6,13, tapi setelah evaluasi pada siklus II prestasi siswa menjadi 7,74. Dari temuan menunjukkan bahwa ada peningkatan pemahaman membaca siswa dari siklus I ke siklus II, sedangkan pada siklus I siswa prestasi pemahaman membaca adalah 23, 81, tapi setelah dievaluasi pada siklus II membaca pemahaman siswa menjadi 25, 69. Sementara standar pencapaian target KKM 66. Dari temuan ini, peneliti membuat kesimpulan bahwa dengan menggunakan pendekatan eklektik bisa meningkatkan prestasi pemahaman membaca siswa. Kata Kunci: Pendekatan Eclectik, Meningkatkan, Reading Comprehension